Synergistic Effects of Applying Potassium Nitrate Spray with Putrescine on Productivity and Fruit Quality of Mango Trees cv. Ewais - Abdullah Alebidi; Mahmoud Abdel-Sattar; Laila Y. Mostafa; Alhussein S. A. Hamad; Hail Z. Rihan (Agronomy, 2023)
The current investigation represents of the synergistic effects of application of potassium nitrate (KNO3) in combination with putrescine (Put) on flowering, productivity, and fruit quality on Ewais mango (Mangifera indica L.) trees during the seasons 2021/2022 and 2022/2023. The selected trees were sprayed at three different stages, including flower bud differentiation, full bloom, and beginning of the fruit set, with one of the following treatments: control, 2% KNO3, 4% KNO3, 50 ppm Put, 75 ppm Put, 2% KNO3 + 50 ppm Put, 2% KNO3 + 75 ppm Put, 4% KNO3 + 50 ppm Put, 4% KNO3 + 75 ppm Put. Results showed that all treatments were successful in improving the productivity of mango trees by increasing flowering terminal shoots, fruit set, fruit retention, number of fruits/tree, yield, and fruit yield increment while reducing the percentage of fruit drop, as well as improving the quality of mango fruits cv. Ewais by increasing fruit length, fruit diameter, TSS, total sugars, V.C, and total phenol and carotenoid content, but at the same time, diminishing the total acidity, as compared with control. Based on this research, the application of 4% KNO3 in conjunction with 75 ppm Putrescine has shown the most prominent advances in enhancing Ewais tree productivity and fruit quality. The investigation successfully highlighted the synergistic effect of using KNO3 and putrescine to improve mango fruit yield and quality.